HETEROGENEOUS HEAT PRODUCTION IN THE EARTH'S UPPER MANTLE: BLOB MELTING AND MORB COMPOSITION - Vlastelic I.; Bougault H.; Dosso L. (My University, 2002)
The existence of heat-producing elements (U, Th, K) and their highly heterogeneous distribution in the Earth's mantle suggests a link between thermal and chemical properties of the mantle. Previous studies have shown that this chemical-thermal relationship has a strong influence on the mantle convection pattern and structure. Here, we investigate the influence of this relationship on mantle melting and chemical variations in mid-ocean ridge basalts (MORB). We use a model of convection in which mantle heterogeneities are considered as enriched blobs (enrichment factor of ~1.8 relative to the bulk silicate Earth) within a convecting depleted medium.Our results explain the first-order chemical variations in MORB in terms of coupled compositional-thermal variations in the underlying mantle source. A consequence is that enriched MORB are formed by larger partial melting extent than depleted MORB. We show that: (1) excess temperatures of up to 100°C are produced in the centers of large (300 km radius) and enriched blobs, and these lead to a 10% increase in the degree of melting. Such large blobs could produce long-wavelength chemical anomalies in MORB whose amplitude, however, is attenuated by extensive melting. Small blobs (radius <100 km), in which only minor temperature excesses (ΔΤ<10°C) develop, may be the cause of high-amplitude chemical spikes along spreading ridges. (2) The maximum temperature gradient within blobs is lower than the solidus slope, which causes the blob to melt progressively from top to bottom. (3) Source enrichment and the degree of melting are positively correlated but the two parameters have competing effects on MORB composition. Normally the source effect is more important than the melting effect. (4) Melting of homogeneous blobs results in a U-shaped chemical anomaly in MORB, the less enriched liquids corresponding to the maximum thermal anomaly. Blobs containing a chemical gradient, with the more depleted composition towards the periphery, may result from entrainment of surrounding depleted mantle. Such blobs, which are thermally more stable, could produce the hump-shaped chemical anomalies commonly observed along mid-ocean ridges.
Keywords: UPPER MANTLE; HEAT SOURCES; MELTING; MID-OCEAN RIDGE BASALTS